2008
DOI: 10.1590/s1809-29502008000400003
|View full text |Cite
|
Sign up to set email alerts
|

Perfil da fisioterapia na reabilitação cardiovascular no Brasil

Abstract: O estudo visou conhecer o modelo de atuação da fisioterapia em reabilitação cardiovascular (RC) no Brasil, bem como o perfil profissional do fisioterapeuta que trabalha com RC e o perfil administrativo dos serviços de RC. Foram obtidas 67 respostas a um questionário disponibilizado na internet durante 2005, consistindo em 52 perguntas fechadas sobre a RC: 25 questões referentes ao modelo de atuação, 14 aos procedimentos de avaliação, 3 ao perfil acadêmico e profissional da equipe, 6 à administração do serviço … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 18 publications
0
5
0
7
Order By: Relevance
“…11 However, it is known that most Brazilians do not have access to CR programs and resources for prevention of cardiovascular diseases are insufficient across the country. 12,13 Indeed, data on the availability and characteristics of CR programs in Brazil are scarce 14 and there is no national or state registry. 15 It is important to show the reality of CR in Brazil, which will contribute to CR advocacy.…”
Section: Introductionmentioning
confidence: 99%
“…11 However, it is known that most Brazilians do not have access to CR programs and resources for prevention of cardiovascular diseases are insufficient across the country. 12,13 Indeed, data on the availability and characteristics of CR programs in Brazil are scarce 14 and there is no national or state registry. 15 It is important to show the reality of CR in Brazil, which will contribute to CR advocacy.…”
Section: Introductionmentioning
confidence: 99%
“…In the United States, only 10 to 20% of the eligible patients participated in a CR program ( 9 11 ) , and among the patients referred who initiated the program, 40 to 50% drop out before finishing it ( 12 ) . It is known that personal, professional, and institutional barriers, as well the motivational level may strongly interfere in participation and compliance ( 13 15 ) .…”
Section: Introductionmentioning
confidence: 99%
“…It is observed that in the physiotherapy team, over the years, there has been greater diversity among its specialties, expanding the range of action options in the hospital environment. Today, the physiotherapy professional is inserted in all care sectors in the hospital context, treating patients of low, medium and high complexity in all stages of hospitalization (Mair et al, 2008).…”
Section: Type Of Hospital Rehabilitationmentioning
confidence: 99%